Pleomorphic adenoma of the palate: A case report and review of a rare entity - Kamala Rawson; Basavaraj N Kallalli; Kalpana Gokul; Ankur Singh (Wolters Kluwer Medknow Publications, 2016)
Pleomorphic adenoma (PA) is the most common benign mixed salivary gland neoplasm that accounts for 60% of all benign salivary gland tumors. It has a diverse histological presentation and occurs in both major and minor salivary glands. PA of minor salivary gland in the palate is a common entity. We report the case of a 40-year-old female who presented with a painless, slow growing swelling of the palate over the last 2 years. Computed tomography (CT) scan revealed an isodense structure in the palate. CT scan showed no signs of bony erosion of the palatal region. Incisional biopsy report revealed PA of the palate. The entire tumor mass was excised along with the overlying mucosa. Histopathological examination confirmed the diagnosis of PA of minor salivary gland. There has been no recurrence of the lesion since 1 year.